Flow Diverters for Intracranial Aneurysms: The DIVERSION National Prospective Cohort Study. Issue 12 (December 2019) - Gory, Benjamin; Berge, Jerome; Bonafé, Alain; Pierot, Laurent; Spelle, Laurent; Piotin, Michel; Biondi, Alessandra; Cognard, Christophe; Mounayer, Charbel; Sourour, Nader; Barbier, Charlotte; Desal, Hubert; et al.
Abstract : Background and Purpose—: Flow diverters are used for endovascular therapy of intracranial aneurysms. We did a nationwide prospective study to investigate the safety and effectiveness of flow diversion at 12 months. Methods—: DIVERSION was a national prospective cohort study including all flow diverters placement between October 2012 and February 2014 in France. The primary end point was the event-free survival rate at 12 months, defined as the occurrence of morbidity (intracranial hemorrhage, ischemic stroke, noncerebral hemorrhage, or neurological deficit due to mass effect), retreatment, or death within 12 months post-treatment. A quality control was carried out on 100% of the collected data and of at least 10% of the included patients in each center, chosen at random. All reported serious events were adjudicated by an independent Data Safety and Monitoring Board. Satisfactory occlusion was defined as 3 or 4 on Kamran scale by an independent imaging core laboratory at 12 months. Results—: We enrolled 398 patients harboring 477 intracranial aneurysms. At least 1 morbidity-mortality event was noted in 95 of 408 interventions representing an event-free survival rate of 75.7% (95% CI, 71.1–79.7). The rate of permanent-related serious events and mortality was 5.9% and 1.2% at 12 months, respectively. Multivariate analysis showed that high baseline blood pressure (hazard ratio, 2.54; 95% CI, 1.35–4.79; P =0.039), diabetes mellitus (hazard ratio, 3.70; 95% CI, 1.60–8.6; P =0.0022), and larger aneurysms (hazard ratio, 1.07; 95% CI, 1.04–1.11; P <0.0001) were associated with the occurrence of a neurological deficit. The satisfactory occlusion rate at 12 months was 79.9%, and the absence of high baseline blood pressure (odds ratio, 2.01; 95% CI, 1.12–3.71; P =0.0193) and postprocedural satisfactory occlusion (odds ratio, 2.75; 95% CI, 1.49–5.09; P =0.0012) were associated with a 12-month satisfactory occlusion. Conclusions—: A satisfactory occlusion was achieved in almost 80% of cases after flow diverter treatment with a permanent-related serious event and mortality rates of 5.9% and 1.2% at 12 months, respectively. Abstract : Supplemental Digital Content is available in the text.